Child Abuse and Aggressive Behavior among Primary School Children - Fatma N. Kotb; Sanaa M. Ahmed (Evidence-Based Nursing Research)
Context: Child abuse considered all forms of physical, emotional, sexual abuse, and neglect. Child abuse identified to threaten development, health, dignity, or even survival. Many abused children have ongoing troubles with relationships, trust in others, difficulties at school, and exhibiting aggressive behavior or act nasty towards other children and animals.